2022
DOI: 10.1002/acp.3999
|View full text |Cite
|
Sign up to set email alerts
|

Black‐and‐white thinking and conspiracy beliefs prevent parents from vaccinating their children against COVID‐19

Abstract: Understanding predictors of parents' willingness to vaccinate their children appears fundamental to promote vaccine acceptability, especially in a pandemic scenario. The present study aimed to investigate the role of conspiracy beliefs and absolutist thinking in parental attitude toward COVID‐19 vaccine, and the predictive role of parents' individual differences on decisions against children's vaccination. An online survey was administered to 415 parents of children aged 5–11, at the very beginning of the vacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…A recent cross-sectional study found that willingness to vaccinate children for COVID in the US before those vaccines were authorized for this age group was inversely related to belief in various vaccine conspiracies (Allen et al, 2023). A study in Italy found a similar result (Iannello et al, 2022). Using a panel in existence since April 2021, we assessed a general conspiratorial mindset at the first wave to see whether it would predict willingness to recommend giving a COVID-19 vaccine to a child ages 5-11 in January and March of 2022, several months after those vaccines were authorized for that age group.…”
Section: Introductionmentioning
confidence: 89%
“…A recent cross-sectional study found that willingness to vaccinate children for COVID in the US before those vaccines were authorized for this age group was inversely related to belief in various vaccine conspiracies (Allen et al, 2023). A study in Italy found a similar result (Iannello et al, 2022). Using a panel in existence since April 2021, we assessed a general conspiratorial mindset at the first wave to see whether it would predict willingness to recommend giving a COVID-19 vaccine to a child ages 5-11 in January and March of 2022, several months after those vaccines were authorized for that age group.…”
Section: Introductionmentioning
confidence: 89%
“…Individuals who endorse conspiracy theories often exhibit a cognitive style characterized by black‐and‐white thinking, which involves viewing the world in stark, polarized terms. This cognitive pattern tends to oversimplify complex issues, events, and interpersonal dynamics into clear‐cut categories of right versus wrong or good versus evil (Iannello et al, 2022). As a result, individuals prone to black‐and‐white thinking may struggle to appreciate the nuances and complexities inherent in emotional experiences.…”
Section: Introductionmentioning
confidence: 99%